Electrophysiological and Neurochemical Considerations of Distinct Neuronal Populations in the Rat Pedunculopontine Nucleus and Their Responsiveness Following 6-Hydroxydopamine Lesions - Wang, Xuenan; Geng, Xiwen; Li, Min; Xie, Jinlu; Chen, Dadian; Han, Hongyu; Meng, Xiaoqian; Yao, Xiaomeng; Zhang, Haiyan; Gao, Yunfeng; Chang, Hongli; Zhang, Xiao; et al. (Frontiers in Neuroscience, 2019)
The pedunculopontine nucleus (PPN) is composed of a morphologically and neurochemically heterogeneous population of neurons, which is severely affected by Parkinson’s disease (PD). However, the role of each subtype of neurons within the PPN in the pathophysiology of PD has not been completely elucidated. In this study, we present the discharge profiles of three classified subtypes of PPN neurons and their alterations after 6-hydroxydopamine (6-OHDA) lesion. Following 6-OHDA lesion, the spike timing of the Type II (GABAergic) and Type III (glutamatergic) neurons had significant phase-lock with the oscillations in the delta and beta band frequency range in the PPN, respectively. Morphological evidence showed distinct alteration in three kinds of neurons after 6-OHDA lesion. These findings revealed that the changes in the firing characteristics of neurons in PPN in hemi-parkinsonism rats are closely associated with damaged neuronal morphology, which would make contributions to the divergence of dysfunctions in Parkinsonism.